Influence of Titanium Alloy Scaffolds on Enzymatic Defense against Oxidative Stress and Bone Marrow Cell Differentiation - Lais Morandini Rodrigues; Elis Andrade Lima Zutin; Elisa Mattias Sartori; Daniela Baccelli Silveira Mendonça; Gustavo Mendonça; Yasmin Rodarte Carvalho; Luana Marotta Reis de Vasconcellos (International Journal of Biomaterials, 2020)
Studies have been directed towards the production of new titanium alloys, aiming for the replacement of Ti-6 Aluminium-4 Vanadium (TiAlV) alloy in the future. Many mechanisms related to biocompatibility and chemical characteristics have been studied in the field of implantology, but enzymatic defenses against oxidative stress remain underexplored. Bone marrow stromal cells have been explored as source of cells, which have the potential to differentiate into osteoblasts and therefore could be used as cells-based therapy. The objective of this study was to evaluate the activity of the antioxidant enzymes superoxide dismutase (SOD) and catalase (CAT) in porous scaffolds of Ti-6 Aluminium-4 Vanadium (TiAlV), Ti-35 Niobium (TiNb), and Ti-35 Niobium-7 Zirconium-5 Tantalum (TiNbZrTa) on mouse bone marrow stromal cells. Porous titanium alloy scaffolds were prepared by powder metallurgy. After 24 hours, cells plated on the scaffolds were analyzed by scanning electron microscopy (SEM). The antioxidant enzyme activity was measured 72 hours after cell plating. Quantitative real time PCR (qRT-PCR) was performed after 3, 7, and 14 days, and Runx2 (Runt-related transcription factor2) expression was evaluated. The SEM images showed the presence of interconnected pores and growth, adhesion, and cell spreading in the 3 scaffolds. Although differences were noted for SOD and CAT activity for all scaffolds analyzed, no statistical differences were observed (p>0.05). The osteogenic gene Runx2 presented high expression levels for TiNbZrTa at day 7, compared to the control group (TiAlV day 3). At day 14, all scaffolds had more than 2-fold induction for Runx2 mRNA levels, with statistically significant differences compared to the control group. Even though we were not able to confirm statistically significant differences to justify the replacement of TiAlV regarding antioxidant enzymes, TiNbZrTa was able to induce faster bone formation at early time points, making it a good choice for biomedical and tissue bioengineering applications.